As influências do direito internacional da água, mais particularmente das SOFT LAW, sobre a construção do tratado de cooperação amazônica - Fonseca, Alan Kelson de Lima (2023)
This dissertation analyzes the influences that the Amazon Cooperation Treaty suffered from the International Water Law. Despite the Amazon Cooperation Treaty not having assimilated concepts rooted in International Water Law, such as the definition of basin of international drainage or international river, represents a strong expression of the norms international issues, such as environmental preservation and protection, even ensuring the sovereignty of Amazon States, since this was its main focus. The reasons why the Treaty has privileged sovereignty is in the frequent international discourses that preach the internationalization of the Amazon, under the false premise that the Amazon States, through their governments, would not have the capacity to manage environmental assets, putting the international community, especially in the future maintenance of these assets. The insistence on expropriation of Amazonian assets, which result from their enormous dimensions and fantastic riches of all shades have always been a constant in the Amazonian reality, since the first explorations by colonizers, which is evaluated in the text, in a separate chapter on the Amazon. The text evaluates the environmental issue, from the perspective that it represents a change in paradigm in Law; demonstrates the growing concern of countries with the availability and water quality, which has generated international cross-border conflicts; reports the terms the construction of the Amazon Cooperation Treaty and the difficulties in its implementation; It is, as a conclusion, it evaluates the importance of the norms of International Water Law in the Treaty of Amazon Cooperation, and the strong contribution of the terms of the Treaty in Law Water International.